A retrospective record review of the impact of intellectual disability on the forensic observation process - Van Rooyen, L.J. (My University, 2015)
Background: It is estimated that, in South Africa, 11% of referrals for forensic psychiatric observation have intellectual disability. Assessments are challenging in this group due to cognitive limitations. The impairment may impact on their fitness to stand trial, whether they were able to appreciate the wrongfulness of the offence that they were charged with and if they were able to act accordingly. Depending on the degree to which intellectual disability affects fitness to stand trial and accountability, a recommendation has to be made regarding whether the observandi should be referred back to the criminal judicial system or whether they should be admitted to a psychiatric hospital for further management. Objectives: To identify and describe a group of individuals with intellectual disability admitted to Sterkfontein Hospital (SFH) for forensic observation during a specified study period, in terms of their demographic and clinical characteristics and investigate these characteristics in terms of the nature of the alleged crimes committed and in terms of the outcome of their forensic assessment, namely their capacity to stand trial and the measure of their criminal responsibility. Method: A retrospective record review was conducted, including observandi with intellectual disability referred to SFH during 2011 and 2012. Information was obtained from the summary of the forensic observation findings in their files. Statistics were mostly descriptive but a statistician was consulted to compare the degree of disability with the outcome of the observation process. Results: The study found that 8.7% of referrals had intellectual disability. The majority of subjects were between 21 and 30 years old (49.0%), male (96.1%), single (98.0%) and unemployed (76.5%). Only 31.4% were educated in special schools while 39.2% never progressed beyond primary school. The degree of disability was moderate in 51.0% and mild in 43.1%. The most common charge was rape (45.1%). Medical co morbidities were diagnosed in 21.6% of cases with and an equal percentage of psychiatric co-morbidities were present. The majority of observandi were not fit to stand trial and not accountable (62.7%). In the majority of cases (66.7%), referral for further management, i.e. involuntary admission to a psychiatric facility under the Mental Health Care Act, was recommended. A strong association between the degree of disability and the outcome of the process was found (p<0.001). Conclusions: Although intellectual disability impacts on fitness to stand trial and accountability, observandi with disability may be fit to stand trial and/or have criminal responsibility. An association exists between the degree of impairment and the outcome of the forensic psychiatric observation process, but categorizing observandi according to the level of disability may be difficult and objective methods of doing this is often not applied. The degree of disability tends to correlate with the outcome, but this is not always the case. The recommendation made following observation is important in terms referral to appropriate facilities as this may improve risk management.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Medicine in the branch of Psychiatry, Johannesburg, 2015